Protocol for generating and characterizing a nasal epithelial model using imaging with application for respiratory viruses - Victor H.K. Lam; Aleena Ghafoor; Yazan Khan; Shirley Constable; Lane B. Buchanan; David Zuanazzi; Reeya Parmar; Zeynep G. Tepe; Leigh J Sowerby; Cindy M. Liu; Ryan M. Troyer; Jessica L. Prodger (STAR Protocols)
Summary: Air-liquid interface (ALI) culture can differentiate airway epithelial cells to recapitulate the respiratory tract in vitro. Here, we present a protocol for isolating and culturing nasal epithelial cells from turbinate tissues for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We describe steps to overcome challenges of imaging fragile cultures, detect the production of mucus, and quantify intracellular virus post-SARS-CoV-2 infection. We present data on the optimal duration of ALI maturation prior to experimentation and describe which steps can be altered to optimize testing of specific hypotheses. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.